Critical factors for diffusion of web technologies for supply chain management functions: Malaysian perspective - Tarofder, Arun Kumar; Marthandan, Govindan; Haque, A. K. M. Ahasanul (EuroJournals Publishing, Inc., 2010)
Good supply chain management is essential for a successful company. Supply chain management can reach beyond the boundaries of a single company to share that information between suppliers, manufacturers, distributors, and retailers. This is where the information technologies play an important role. Information technology (IT) facilitates companies to share of large amounts of information along the supply chain, and is often referred to as vital facilitator of supply chain management (SCM) functions. As a new medium of communication, the Internet has conquered the world with break taking speed, and it’s the worldwide penetration and high level of standardization contributes to increase globalization. With new web technologies, Internet based systems can deliver functionality and information to user a standard web browser, thereby eliminating requirement for traditional Electronic Data Interchange (EDI) or client based software and reducing information technology implementation and maintenance costs, cycles and burdens. The Internet offers the supply chain immense potential and entirely new ways for streamlining coordination between business partners and customers. Therefore, this study explores the use of use technologies for organizational SCM. Based on an extensive survey of Malaysian organizations, it investigates the diffusion of web technologies into supply chain functions. The findings suggested that top management support and Trialability play crucial role for diffusing web technologies in supply chain. This study provides a greater understanding of managers’ perception of web technologies diffusion in their organizations. Those interested in adopting web technologies in their supply chain activates may find these results helpful in guiding their effort.